Economic Contributions of Agriculture, Natural Resources, and Food Industries in Florida in 2013 - Alan W. Hodges; Mohammad Rahmani; Thomas J. Stevens (EDIS)
About 1.52 million people worked full- or part-time in Florida’s agriculture, natural resources and food industries in 2013— an 8.7 percent increase in jobs over 2012.